Carbon and Hydrogen Isotopic Reversals in Highly Mature Coal-Derived Gases: A Case Study of Paleozoic Gases in the Southern Ordos Basin, China - Dan Liu (Geofluids)
The compositional carbon isotopic series δ13C-CH4<δ13C-C2H6<δ13C-C3H8<δ13C-C4H10 is common in thermogenic gases. With the exploration of deeper strata, however, isotopic reversals (δ13C-CH4>δ13C-C2H6>δ13C-C3H8) in overmature unconventional shale gases and conventional (coal-derived) gases have been identified. Paleozoic gases in the southern Ordos Basin, China, with partial or complete isotopic reversals, were studied as examples of isotopic fractionation in overmature coal-derived gases. Isotopic compositions of gases of different maturities from the Ordos Basin and shale gases from around the world were compared. Results indicate that carbon isotopic series are related to maturity. Complete isotopic reversal occurs mostly in regions with vitrinite reflectance Ro>2.4%. Where 2.4%>Ro>2.0%, almost all gases display partial isotopic reversal, with δ13C-CH4>δ13C-C2H6 or δ13C-C2H6>δ13C-C3H8. Carbon isotopic reversal in coal-derived gases is not caused by abiotic origin, the mixing of gases from different types of source rock, abiotic polymerization, wet gas cracking, and other mechanisms that contribute to reversal in shale gases. Based on the unique structure of coaly source rock and the geology of the Ordos Basin, closed-system aromatization-polycondensation reactions are considered the most likely cause of carbon isotopic reversal. During the reactions, isotopically light gases are generated by recombination of previously formed hydrocarbons and residual kerogen-coal. Hydrogen isotopic reversal in the southern Ordos Basin might also be caused by aromatization-polycondensation reactions.